2021
DOI: 10.34172/jcs.2021.010
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Multiple Sclerosis patients: A Concept Analysis Using the Evolutionary Method

Abstract: Introduction:Health literacy is one of the effective factors in health promotion of chronic patients. However, little attention has been paid to it; no exact and clear definition of health literacy has ever been accessible in chronic diseases. This study was conducted with aim of defining and clarifying attributes, antecedents, and consequences of health literacy in multiple sclerosis (MS) patients. Methods: Rodgers’ evolutionary method of concept analysis was used to clarify the concept of health litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The studies used various terms to describe a concept analysis (Table 1). The studies included those that analysed HL (Mancuso, 2008; Parnell et al, 2019; Speros, 2005), critical HL (Sykes et al, 2013), lay worker HL (Cadman, 2017) and HL in relation to health outcomes (Sierra & Cianelli, 2019), shaping alcohol HL (Okan et al, 2020), HL in patients with multiple sclerosis (Dehghani, 2021), HL in older adult populations (Oldfield & Dreher, 2010) and concept analysis of HL for patients with CVD (Sim & Hwang, 2019). The concept analysis methods included the hybrid method (Sim & Hwang, 2019), Roger's method (Dehghani, 2021; Mancuso, 2008), Walker and Avant's method (Oldfield & Dreher, 2010; Parnell et al, 2019; Sierra & Cianelli, 2019; Speros, 2005), the evolutionary method (Okan et al, 2020; Sykes et al, 2013) and Wilson's methods (Cadman, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies used various terms to describe a concept analysis (Table 1). The studies included those that analysed HL (Mancuso, 2008; Parnell et al, 2019; Speros, 2005), critical HL (Sykes et al, 2013), lay worker HL (Cadman, 2017) and HL in relation to health outcomes (Sierra & Cianelli, 2019), shaping alcohol HL (Okan et al, 2020), HL in patients with multiple sclerosis (Dehghani, 2021), HL in older adult populations (Oldfield & Dreher, 2010) and concept analysis of HL for patients with CVD (Sim & Hwang, 2019). The concept analysis methods included the hybrid method (Sim & Hwang, 2019), Roger's method (Dehghani, 2021; Mancuso, 2008), Walker and Avant's method (Oldfield & Dreher, 2010; Parnell et al, 2019; Sierra & Cianelli, 2019; Speros, 2005), the evolutionary method (Okan et al, 2020; Sykes et al, 2013) and Wilson's methods (Cadman, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The studies used various terms to describe a concept analysis (Table 1). The studies included those that analysed HL (Mancuso, 2008;Parnell et al, 2019;Speros, 2005), critical HL (Sykes et al, 2013), lay worker HL (Cadman, 2017) and HL in relation to health outcomes (Sierra & Cianelli, 2019), shaping alcohol HL (Okan et al, 2020), HL in patients with multiple sclerosis (Dehghani, 2021), HL in older adult populations (Oldfield & Dreher, 2010) and concept analysis of HL for patients with CVD (Sim & Hwang, 2019).…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, limited health literacy will affect people’s behaviour related to self-management of chronic conditions, outcomes of health efforts (Sántha, 2021), and health costs in society (Dehghani, 2021). Several studies have also revealed that inadequate health literacy can lead to poor health implications, unsuccessful preventive care, and high health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…The processing and assessment of health literacy are influenced by the complexity of the information, jargon, and partial understanding of the information. Dehghani (2021) states that the evaluation of health information is critical in applying health literacy. If the review of health information is not carried out properly, it will cause difficulties in using the information as a basis for decision-making.…”
Section: Appraisementioning
confidence: 99%